1998
DOI: 10.1523/jneurosci.18-16-06512.1998
|View full text |Cite
|
Sign up to set email alerts
|

Appetitive and Consummatory Male Sexual Behavior in Japanese Quail Are Differentially Regulated by Subregions of the Preoptic Medial Nucleus

Abstract: Central testosterone aromatization is required for the activation of both appetitive (ASB) and consummatory (CSB) male sexual behavior in Japanese quail. There are two major clusters of aromatase immunoreactive (ARO-ir) cells in the rostral forebrain; these outline the nucleus preopticus medialis (POM) and the nucleus striae terminalis (BST). We investigated the role of these nuclei in the regulation of ASB and CSB. Appetitive male sexual behavior was measured with the use of a learned social proximity procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
182
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 189 publications
(200 citation statements)
references
References 49 publications
16
182
2
Order By: Relevance
“…These responses are not expressed in castrated males and are restored to rates observed in intact sexually mature males by treatments with exogenous testosterone [6,25,29,63]. As mentioned above, effects of testosterone on these two measures of ASB require aromatization of the androgen [28,136].…”
Section: The Medial Preoptic Area Is Also Implicated In the Control Omentioning
confidence: 91%
See 3 more Smart Citations
“…These responses are not expressed in castrated males and are restored to rates observed in intact sexually mature males by treatments with exogenous testosterone [6,25,29,63]. As mentioned above, effects of testosterone on these two measures of ASB require aromatization of the androgen [28,136].…”
Section: The Medial Preoptic Area Is Also Implicated In the Control Omentioning
confidence: 91%
“…[25,29,67]). In both species, the action of testosterone on ASB also seems to be mediated by its aromatization into an estrogen.…”
Section: The Medial Preoptic Area Is Also Implicated In the Control Omentioning
confidence: 99%
See 2 more Smart Citations
“…We quantitatively studied AR mRNA expression in the preoptic area (including different nuclei in the medial and lateral preoptic area), the BnST (bed nuclei of stria terminalis), the ventral pallidum, and the lateral septum. Previous research has shown that these nuclei contain androgen receptors and are involved in social, aggressive and copulatory behaviors [4,10,15,19,46,47] and might therefore represent nuclei that are possibly involved in early chick behavior.…”
Section: Introductionmentioning
confidence: 99%